2021
DOI: 10.1152/ajpregu.00121.2021
|View full text |Cite
|
Sign up to set email alerts
|

Body mass-normalized moderate dose of dietary nitrate intake improves endothelial function and walking capacity in patients with peripheral artery disease

Abstract: Peripheral artery disease (PAD) is characterized by the accumulation of atherosclerotic plaques in the lower extremity conduit arteries, which impairs blood flow and walking capacity. Dietary nitrate has been used to reduce blood pressure (BP) and improve walking capacity in PAD. However, a standardized dose for PAD has not been determined. Therefore, we sought to determine the effects of a body mass-normalized moderate dose of nitrate (0.11 mmol nitrate/kg) as beetroot juice on serum nitrate/nitrite, vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 80 publications
1
33
1
Order By: Relevance
“… 172 In this context, beetroot juice may improve both endurance and power exercise performance through increasing NO bioavailability, which in turn modulates mitochondrial respiration, reduces oxygen cost of exercise, and improves muscular and cerebral perfusion. 173 , 174 Recent evidence has shown that the stimulation of the nitrate-nitrite-NO pathway by beetroot juice consumption may improve endothelial function, as measured by flow-mediated dilation, in persons with or at risk of endothelial dysfunction, including older adults, 175 people with peripheral artery disease, 176 pregnant women, 177 and persons with hypercholesterolemia 178 and hypertension. 179 Moreover, beetroot juice ingestion was associated with a reduction in blood pressure in normotensive 180 and hypertensive people, 181 and in older adults.…”
Section: Discussionmentioning
confidence: 99%
“… 172 In this context, beetroot juice may improve both endurance and power exercise performance through increasing NO bioavailability, which in turn modulates mitochondrial respiration, reduces oxygen cost of exercise, and improves muscular and cerebral perfusion. 173 , 174 Recent evidence has shown that the stimulation of the nitrate-nitrite-NO pathway by beetroot juice consumption may improve endothelial function, as measured by flow-mediated dilation, in persons with or at risk of endothelial dysfunction, including older adults, 175 people with peripheral artery disease, 176 pregnant women, 177 and persons with hypercholesterolemia 178 and hypertension. 179 Moreover, beetroot juice ingestion was associated with a reduction in blood pressure in normotensive 180 and hypertensive people, 181 and in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The main characteristic of the 15 studies included in the review are summarized in Table 1 [56][57][58][59][60][61] and Table 2 [62][63][64][65][66][67][68][69][70]. Specifically, Table 1 reports the results of acute interventions (n = 6), and Table 2 reports the results related to the chronic dietary interventions (n = 9).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Specifically, Table 1 reports the results of acute interventions (n = 6), and Table 2 reports the results related to the chronic dietary interventions (n = 9). The majority of the studies (n = 7) were performed in the USA [57][58][59][60]62,67,68]. Of the remaining studies, four were conducted in the UK [61,65,66,69], two studies were performed in Australia [63,64], and two in Brazil [56,70].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations